Critical criteria for sediment suspension derived from suspension probability - Lixia Sun; Zhongwu Jin; Zhilin Sun; Guiying Shen; Haolei Zheng; Chao Guo; Lingyun Li (Engineering Science and Technology, an International Journal)
The critical criterion of sediment suspension is a key problem in hydraulic engineering, environmental protection and coastal engineering, which plays a significant role in the numerical computations of suspended sediment motion. This study explored the critical suspension for nonuniform sediment through theoretical derivation and flume experiments. First, two criteria were proposed based on the suspension probability from the perspectives of dynamics and kinematics, respectively. Then, the flume experiment was conducted with nonuniform dyeing sediment and a high-speed camera. Finally, the criteria were verified by the experimental data and compared with several other criteria. It was found that the two criteria of dynamics and kinematics are functions of relative suspension velocity and suspension parameters, respectively. The interaction coefficient of nonuniform sediment is introduced into the two criteria and reflected in the suspension and settling velocities, respectively. The result of this study is a step forward in theory compared with the critical criterion of uniform sediment suspension.